2007
DOI: 10.1111/j.1834-7819.2007.tb00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience among 45–54 year olds in Adelaide, South Australia

Abstract: Background: Middle-aged adults are an important focus of dental policy with increasing retention of teeth and use of dental services. The aims of the study were to describe the caries experience of 45-54 year olds by dental visit pattern, dental behaviour, socio-demographics and socio-economic status. Methods: A random sample of 45-54 year olds from Adelaide, South Australia was surveyed by selfcomplete questionnaire during 2004-2005 with up to four follow-up mailings to non-respondents (n = 879, response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Some key demographic characteristics from the Census showed a close approximation to that observed in the study. 10,11 Comparison with other sample data showed a range of generally small differences between these data and the study participants, and reliability of the clinical measures was reported to be good to excellent.…”
Section: Representativeness and Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Some key demographic characteristics from the Census showed a close approximation to that observed in the study. 10,11 Comparison with other sample data showed a range of generally small differences between these data and the study participants, and reliability of the clinical measures was reported to be good to excellent.…”
Section: Representativeness and Reliabilitymentioning
confidence: 99%
“…10,11 The implications of a focus on individual knowledge and behaviour need to be considered cautiously. Lifestyle interventions have been criticised for their limited effectiveness in producing sustained improvements in oral health or for reducing oral health inequalities.…”
Section: Oral Disease and Lifestyle Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For studies conducted in South Vietnam [7] and China [9], females had increased risk of caries lesions, greater chance for sealed and lower risk to being missing, in Bulgaria females had greater risk for missing teeth and filled teeth. The study in South Australia [11] (n= 709) found that males had fewer risk for missing teeth, unlike Brazil study [12] (n = 1159) where males had a greater risk for missing teeth and increased risk of carious lesions. The benefits in the oral health are directly reflected in better chewing ability of the adult population when the molars are presented [13].…”
Section: Introductionmentioning
confidence: 79%
“…Sanders et al reported that dental missing increased with increasing age and associated with the people economic state (13). The DMFT index was related to healthy behavior, dental visits and income level in Australia (11) and France (14).…”
Section: Introductionmentioning
confidence: 99%